Effects of ambient and preceding temperatures and metabolic genes on flight metabolism in the Glanville fritillary butterfly - Wong, Swee Chong (J Insect Physiol, 2016)
Flight is essential for foraging, mate searching and dispersal in many insects, but flight metabolism in ectotherms is strongly constrained by temperature. Thermal conditions vary greatly in natural populations and may hence restrict fitness-related activities. Working on the Glanville fritillary butterfly (Melitaea cinxia), we studied the effects of temperature experienced during the first 2 days of adult life on flight metabolism, genetic associations between flight metabolic rate and variation in candidate metabolic genes, and genotype–temperature interactions. The maximal flight performance was reduced by 17% by 2 days of low ambient temperature (15 °C) prior to the flight trial, mimicking conditions that butterflies commonly encounter in nature. A SNP in phosphoglucose isomerase (Pgi) had a significant association on flight metabolic rate in males and a SNP in triosephosphate isomerase (Tpi) was significantly associated with flight metabolic rate in females. In the Pgi SNP, AC heterozygotes had higher flight metabolic rate than AA homozygotes following low preceding temperature, but the trend was reversed following high preceding temperature, consistent with previous results on genotype–temperature interaction for this SNP. We suggest that these results on 2-day old butterflies reflect thermal effect on the maturation of flight muscles. These results highlight the consequences of variation in thermal conditions on the time scale of days, and they contribute to a better understanding of the complex dynamics of flight metabolism and flight-related activities under conditions that are relevant for natural populations living under variable thermal conditions.